Antibacterial and Antioxidant Activities of Acetogenins from Streptomyces sp. VE2; An Endophyte in Vernonia cinerea (L.) Less. - Thongchai Taechowisan, Chatchadakan Singtotong, Waya S. Phutdhawong (Journal of Applied Pharmaceutical Science, 2016)
Strain VE2 was isolated from the stem tissue of Vernonia cinerea (L.) Less. and identified as Streptomyces sp. on the basis of morphology, chemotaxonomy and 16SrDNA sequencing. The fractionation of the crude ethyl acetate (CEA) extract from VE2 cultures led to the isolation of two acetogenins; squamocin and rollidecin B; these compounds and CEA extract had potential in antibacterial and antioxidant activities. The crude extract showed the highest activity against Salmonella typhi ATCC19430 and Bacillus cereus ATCC7064, with MIC values of 32 µg/ml. Squamocin also showed the lowest MIC (32 µg/ml) and Minimum Bactericidal Concentration (MBC) (128 µg/ml) against S. Typhi and B. cereus with corresponding large diameter of the zone of inhibitions (27.5 and 28.2 mm, respectively). Rollidecin B showed the highest DPPH antioxidant activity with SC50 value of 58.92 µg/ml.
Keywords: Acetogenins, antibacterial activity, antioxidant activity, Streptomyces sp.